«Board Games» Assemblages from Early Agricultural Settlements in South-Eastern Europe - Shatilo, L.O. (Праці Центру пам’яткознавства, 2014)
The article considers the hypothesis that some groups of artefacts (astragalus, «cones» and objects with a system of holes) dating to early agricultural period (Neolithic and Chalcolithic) from the territory of South-Eastern Europe could have been used as equipment for playing ancient «games» or divination practices. The analysis led to several conclusions: 1) the objects from South-Eastern Europe are similar in shape to the artefacts that most researchers consider game equipment (Ancient World, ethnography); 2) these objects appear in agricultural societies, where signifi cant changes in the outlook and self-consciousness of the population could be observed; 3) astragalus, cones and boards with holes appear in the early Neolithic in the Near East and in the SEE region, they could have reached South-Eastern Europe in the process of neolithization; 4) the name «games» for such items can only be used conventionally.